IMPROVING STUDENTS’ SELF-STUDY EXPERTISE DURING THE COVID 19 PANDEMIC AT BINH DUONG UNIVERSITY - Bich, Vu Ngoc; Anh, Nguyen Do Van; Vi, Nguyen Thi Truc; Huong, Tang Minh; Van , Nguyen Thi Hai (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Self-study is widely regarded as the most effective method of determining a student’s learning effectiveness at the university level. The success or failure of the learning process is highly dependent on the learners’ senses, with an awareness of the role and importance of self-study playing a minor role. Students benefit from self-study not only in terms of mastering knowledge, skills, and techniques, and developing the appropriate career attitude, but also in terms of developing their personality, forming habits, and self-study awareness for life. In the current context, with the COVD-19 pandemic still very complicated, the majority of schools have already converted their teaching models to online or other forms of instruction. This change has a significant impact on both teachers’ teaching quality and students’ self-study. This article will analyze several factors affecting students’ self-study capacity, as well as the current state of selfstudy capacity among Binh Duong university students, with the goal of proposing some solutions for capacity improvement. Learners’ self-learning capacity adapted to the Covid-19 pandemic